A comparative study between classically inverted and temporally inverted internal limiting membrane flap technique in the treatment of macular hole - Hassan M. Hegazy; Ashraf M. Gad; Ibrahim F.M. Ibrahim (Al-Azhar Assiut Medical Journal)
Background and aim A full-thickness retinal tissue defect affecting the anatomic fovea and, particularly, the foveola of the eye is referred to as a macular hole. The study’s objective was to compare the visual and anatomical results of using a temporal inverted internal limiting membrane (ILM) flap and a classical inverted ILM flap in the surgical closure of stage IV idiopathic macular holes. Patients and methods A prospective, randomized, interventional, comparative study was conducted at Al-Azhar University hospitals on 40 eyes of 40 patients with macular holes randomized to two groups: group I (20 patients) undergone pars plana vitrectomy with classic inverted ILM flap and group II (20 patients) undergone pars plana vitrectomy with the temporal inverted ILM flap technique. Results In group I, there was statistically insignificant differences (P=0.648) between patients who had dissociated optic nerve fiber layer (DONFL) in their optical coherence tomography (OCT) images (yes group) (mean±SD=0.44±0.08), and patients without DONFL in their OCT images (no group) (mean±SD=0.41±0.12), and same observation found in group II at which there was no statistically significant difference (P=0.874) between patients who had DONFL in their OCT images (yes group) (mean±SD=0.47±0.12), and patients without DONFL in their OCT images (no group) (mean±SD=0.46±0.19). Conclusion There is no significant difference in the postoperative best-corrected visual acuity between the two techniques. The integrity of Ellipsoid zone (EZ) and External limiting membrane (ELM) is essential for the improvement of visual acuity after operation.